Policy Integration and Coordination in COVID-19 Times: A State of the Art - Parra Ramírez, Esther; Bayona-Sarmiento, Manuel (Sociedad y Economía, 2024)
This state-of-the-art analysis provides a review of research production on policy coordination and integration during times of uncertainty and ambiguity, such as the COVID-19 health crisis. A review of studies conducted in Europe and America, particularly between 2015 and 2022, was undertaken. The conclusion drawn is that the implementation of integration and coordination depends on the differences in political systems, social and cultural characteristics, partisan orientations, and leadership styles. Coordination schemes are more feasible in strong central governments, and integration is more frequent in countries with greater sub-regional autonomy. The COVID-19 crisis served as a “litmus test”. Latin America presents greater complexity due to institutional and structural weaknesses that facilitated the concentration of presidential power and the “normalization” of curtailed freedoms, as well as decision-making based on “states of exception”.